METODE PEMBELAJARAN BAHASA ARAB YANG EFEKTIF UNTUK MENINGKATKAN KEMAMPUAN BERCAKAP MAHASISWAFTIK IAIN (Studi pada Jurusan Pendidikan Bahasa Arab) - Ubadah Ubadah (ISTIQRA, 2016)
This research was qualitative design which dealt with the method of Arabic learning effectively to improve the students' speaking skill of Tarbiyah and Teacher Training Faculty of IAIN Palu (the study of Arabic Education Department). The problem statements: what methods and techniques were used by the Arabic lectures in teaching Arabic lecturing at Arabic Educatiaon Department in speaking Arabic, and what methods were effective in improving the students' speaking ability at Arabic Education Department.The research result showed that the method used by the lecturers were various. The students' ability in speaking Arabic was low (under standar). That the method and technique were effective in improving the students' speaking ability was direct method or á¹¬arÄ«qah al-mubasyirah and combined with relevant method